Exploration of Bidayuh basketry plaiting and beadwork techniques to create contemporary fashion accessories - Sherlina, Niponi (Universiti Malaysia Sarawak (UNIMAS), 2012)
The prupose of the research was to create a range of contemporary fashion accessories utilizing both Bidayuh beadwork and basketry plaiting techniques suitable for today's market. Research was done to identify the types of beads and plaiting materials suitable to be use in designing the final products to keep the identity and value of these Bidayuh handicrafts. The data was collected via two main approaches, the first set involves data collection from selected respondents via interviews and the second set through observations and visuals.